BERNARDO PEREIRA DE VASCONCELOS E O CÓDIGO CRIMINAL DE 1830 - Godoy, Arnaldo Sampaio de Moraes (Revista da AJURIS - Qualis A2, 2021)
BERNARDO PEREIRA DE VASCONCELOS AND THE BRAZILIAN CRIMINAL CODE OF 1830 ÁREA(S): direito penal; história do direito. RESUMO: O ensaio apresenta as linhas gerais do pensamento conservador brasileiro do século XIX, na pessoa de Bernardo Pereira de Vasconcelos, autor intelectual do Código Criminal de 1830, texto normativo influenciado pelo utilitarismo de Jeremy Bentham. ABSTRACT: The paper presents the general outlook of the Brazilian conservative thought of the 19th Century, in the efforts of Bernardo Pereira de Vasconcelos, the intellectual author of the Brazilian Criminal Code of 1830, in which one can figure out the influence of Jeremy Benthan´s utilitarism. PALAVRAS-CHAVE: Código Criminal de 1830; Bernardo Pereira de Vasconcelos; primeiro movimento de modernização da justiça criminal brasileira; distanciamento para com os padrões do Livro V das Ordenações Filipinas; influências do pensamento utilitarista. KEYWORDS: Brazilian Criminal Code of 1830; Bernardo Pereira de Vasconcelos; first efforts towards the modernization of the brazilian criminal justice; abandon of the paragons of Book Five from Ordenações Filipinas; utilitarism. SUMÁRIO: Introdução; 1 O contexto histórico, político e social de surgimento do Código Criminal e o papel de Bernardo Pereira de Vasconcelos; 2 A influência do pensamento liberal utilitarista de Jeremy Bentham sobre Bernardo Pereira de Vasconcelos; 3 As linhas gerais do Código Criminal do Império; Conclusões; Referências. SUMMARY: Introduction; 1 The historical, the political and the social context in the emergence of a Criminal Code and the role of Bernardo Pereira de Vasconcelos; 2 The influence of Jeremy Bentham upon Bernardo Pereira de Vasconcelos in the boundaries of the liberal and the utilitarian thought; 3 The general guidelines of the Brazilian Imperial Criminal Code; Conclusions; References.